2010
DOI: 10.1111/j.1365-2435.2010.01740.x
|View full text |Cite
|
Sign up to set email alerts
|

From bivalves to birds: oxidative stress and longevity

Abstract: Summary1. The oxidative stress theory of ageing predicts that animals living longer will have less cumulative oxidative damage together with structural characteristics that make them more resistant to oxidative damage itself. 2. Although a general relationship between body size, metabolism and longevity does not exist in marine invertebrates, they are generally characterized by low rates of metabolism and reactive oxygen species (ROS) formation associated with lower antioxidant enzyme activities compared to ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 109 publications
1
97
0
3
Order By: Relevance
“…The transient reduction of metabolically derived ROS formation during MRD may have life prolonging effects in the ocean quahog Buttemer et al, 2010). Although A. islandica already features very low in vitro ROS formation under normoxic states 3 and 4 (Buttemer et al, 2010), ROS production in isolated gill tissue was found to be drastically reduced under low oxygen conditions of 5kPa compared with 21kPa and supposedly fully subsides as cellular respiration stops at 0kPa.…”
Section: Discussionmentioning
confidence: 93%
“…The transient reduction of metabolically derived ROS formation during MRD may have life prolonging effects in the ocean quahog Buttemer et al, 2010). Although A. islandica already features very low in vitro ROS formation under normoxic states 3 and 4 (Buttemer et al, 2010), ROS production in isolated gill tissue was found to be drastically reduced under low oxygen conditions of 5kPa compared with 21kPa and supposedly fully subsides as cellular respiration stops at 0kPa.…”
Section: Discussionmentioning
confidence: 93%
“…The most probable fitness benefit was an increase in the reproductive lifespan of the worms, since females of O. volvulus (and almost certainly O. ochengi) remain fecund for >10 yr, whereas O. flexuosa is thought to only live for ;1 yr (Plenge-Bönig et al 1995). As reactive oxygen species are one of the principal drivers of aging (Buttemer et al 2010), we propose that the ability of Wolbachia to perform aerobic respiration and to metabolize iron while maintaining an elevated oxidative stress response are key mechanisms that promote infection of somatic tissues in filariae.…”
Section: Discussionmentioning
confidence: 99%
“…Macromolecular damage in adductor muscle could lead to significant organismal consequences, either by limiting an individual's capacity to perform valve gaping behaviours that might contribute to evaporative cooling or by increasing susceptibility to predation. Adjustments in antioxidant capacity likely stem from changes in the rate of ROS formation, potentially mediated by shifts in mitochondrial volume ( plastic over weeks to months; [61]) or by adjustments in the level of unsaturation of fatty acids in the inner mitochondrial membrane [27,33]. These physiological changes would correspond with changes in overall oxygen utilization or in the leakiness of the inner mitochondrial membrane to protons, respectively.…”
Section: (B) Antioxidant Capacities Of All Tissues Respond To Environmentioning
confidence: 99%
“…We specifically quantify the capacity to prevent oxidative stress, which results from an imbalance between the rate of production of reactive oxygen species (ROS) and the cell's antioxidant capacity. The rate of production of ROS is inherently linked to metabolism [32,33], and it tends to increase when organisms are pushed towards their thermal limits and/or when they are exposed to cycles of hypoxia and reoxygenation [32][33][34][35]. Although mussels' physiologies appear well suited to the oxidative stress potentially engendered by their intermittently warm and hypoxic lifestyle (coinciding when the shell valves are closed at low tide; [36,37]), available data support a role for variation in susceptibility to oxidative stress in setting different thermal tolerance limits among Mytilus congeners [38,39].…”
Section: Introductionmentioning
confidence: 99%